Sekuritisasi Pemerintah Kanada era Justin Trudeau dalam Mengatasi Masalah Keamanan Negara akibat Pencemaran Lingkungan di Situs Penambangan Minyak Pasir di Alberta, Kanada 2015-2017 - Akbar, Zulfikar Kharisma; Utomo, Tri Cahyo (Journal of International Relations, 2019)
The development of globalization has made the environmental issue must be notice by the world. Exploration and exploitation in Alberta tar sands oil mining has proven to cause environmental damage which includes the effects of greenhouse gases, air pollution, and water pollution. The impact of environmental damage and pollution due the mining processes has fueled cynical response from international environmental organizations, society, and international regimes to the Government of Canada. In addition, being involved under environmental regime also requires Government of Canada to realize the conditions which has been approved upon the regime. This research aims to explain how the Canadian Government's policies secure environmental pollution in Alberta, Canada tar sands oil mining which had previously been a non-political issue and eventually led to public condemnation. By using a securitization approach, this research describe the efforts and policies of the Canadian Government to secure the threat of environmental damages due to exploration and exploitation of Alberta tar sands oil mining. Canadian Government has made some efforts to securing the case of environmental damage in Alberta tar sands oil mining, but has not reached maximum results.